PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS TAMU HOTEL SYARIAH DI KOTA BANDUNG - Haiqal Darmawan, - (2019)
ABSTRACT The background of this research is based on the phenomenon of the still low level of loyalty of sharia hotel guests in the city of Bandung, one of which is caused by the lack of information that they get and is less developed because sharia hotels are identical with dirty and unsatisfactory facilities. The purpose of this study was to analyze the influence of service quality on the loyalty of sharia hotel guests in the city of Bandung. The location of this study was conducted at 6 Islamic hotels in the city of Bandung. The population in this study were guests of Sharia hotels in the city of Bandung with 110 respondents. The method used in this study is the causality method with a quantitative approach. The data analysis technique used is linear regression. Based on the results of linear regression analysis this study shows that service quality has a positive or significant effect on the loyalty of sharia hotel guests in the city of Bandung. This indicates that the service quality variable directly affects the increase in sharia hotel guest loyalty in the city of Bandung. However, this study implies the need for better service quality in Islamic hotels, especially in the aspect of comfort. This research is expected to provide benefits for sharia-based lodging service business entrepreneurs to be able to continuously improve their service quality strategy. Keywords: Service Quality, CARTER, Loyalty, Business Service Quality, CARTER, Loyalty, Sharia Hospitality